Assessment of the perceptions of tea farmers on the effect of temperature and rainfall variation on tea production in Kisii County - Nyaiyo, Norah Moige; Mamboleo, Dennis Mabeya; Nyantika, Daniel (Research Journal in Advanced Social Sciences, 2021)
Kisii County’s agricultural systems largely depends on rain-fed conditions which are affected by the weather instabilities that cause climate variability. This has led to fluctuations in diverse crop production and in particular tea yields. The study aimed to assess the perceptions of tea farmers on the effect of temperature and rainfall variation on tea production in Kisii County. The study adopted a correlational research design. The sample size was 400 farmers but only 352 farmers returned duly signed questionnaires. The study targeted small scale tea farmers, Kisii Meteorological Department, and three Kenya Tea Development Agency factories of Kisii County. The study used questionnaires to collect primary data from small scale tea farmers and document analysis was used to collect secondary data. Interview schedules were used to collect data from the field service coordinators who were key informants. Primary data collected from small scale tea farmers included their perception on the effect of temperature and rainfall variability on tea production. Purposive and random sampling were used to choose tea factories and farmers respectively. The findings of the study reveals that the perception of the farmers concerning the effects of temperature is that scanty rainfall reduces tea yields, heavy rainfall causes erosion of top soil and washes away available fertilizer thus affecting tea production, and that frostbites reduce tea yields and production significantly since hailstones destroy the tea leaves and reduces tea yields drastically.